2021
DOI: 10.1016/j.aninu.2021.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome analysis of RNA expression profiles reveals the potential regulating action of long noncoding RNA in lactating cows fed a high concentrate diet

Abstract: Subacute ruminal acidosis (SARA) is a common metabolic disease in the dairy farming industry which is usually caused by an excessive amount of high concentrate diet. SARA not only threatens animal welfare but also leads to economic losses in the farming industry. The liver plays an important role in the distribution of nutritional substances and metabolism; however, a high concentrate diet can cause hepatic metabolic disorders and liver injury. Recently, noncoding RNA has been considered as a critical regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Because the liver is an important organ of blood circulation, translocated LPS and LPS binding protein (LBP) eventually enter the liver, leading to liver disease (47). However, in recent years, in-depth studies on the inflammatory response of SARA have found that when dairy cows suffer from SARA, stress is induced and calcium, non-esterified fatty acids, and glucose concentrations are reduced, and glucocorticoid receptor protein in the liver is significantly downregulated, which is consistent with the enrichment results of this experiment (48). Although LPS translocation eventually leads to liver inflammation, liver inflammation after a series of reactions has rarely been explored.…”
Section: Discussionsupporting
confidence: 87%
“…Because the liver is an important organ of blood circulation, translocated LPS and LPS binding protein (LBP) eventually enter the liver, leading to liver disease (47). However, in recent years, in-depth studies on the inflammatory response of SARA have found that when dairy cows suffer from SARA, stress is induced and calcium, non-esterified fatty acids, and glucose concentrations are reduced, and glucocorticoid receptor protein in the liver is significantly downregulated, which is consistent with the enrichment results of this experiment (48). Although LPS translocation eventually leads to liver inflammation, liver inflammation after a series of reactions has rarely been explored.…”
Section: Discussionsupporting
confidence: 87%
“…On the 80th day, before morning feeding, 5 mL of calf blood was collected by vacuuming the caudal vein with heparin sodium anticoagulant, and after standing for 30 min and centrifuging at 3000 r for 10 min to collect serum, it was stored at −80 • C in a refrigerator to determine serum indexes [15]. Serum samples were taken for IgG, α-amylase, ceruloplasmin, trypsin and lysozyme testing.…”
Section: Igg Content and Digestive Enzyme Activity Detectionmentioning
confidence: 99%
“…The transcriptome is considered as the simplified research means for studying the genome, that is, the collection of all transcripts [13,14]. Therefore, RNA-seq is widely used to study the molecular mechanism of feed and to study the genes related to rumen growth and the development of ruminants, which play an important role in promoting rumen morphology and functional development [15,16]. miRNAs regulate the expression of target genes to maintain normal cellular homeostasis, digestion and nutrient absorption in the gastrointestinal tract [15,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations